Game of thrones in class. Effect of gamification on amotivation and perceived quality - Pelegrín-Borondo, Jorge; Sierra-Murillo, Yolanda; Olarte-Pascual, Cristina; García-Milon, Alba (Journal of Management and Business Education, 2020)
The loss of students’ motivation (amotivation) is among the most important problems in academic centers. Nowadays, it is still unknown if gamification diminish the loss of students’ motivation and if it affects the perception of the teaching quality in the classroom. This paper develops an exploratory investigation based on a sample of 57 students, from two subjects, from two different degrees, to analyze whether gamification influences motivation and the perception of the teaching quality in the classroom. Results show that gamification not always reduce amotivation and it may even cause an increase in amotivation. Moreover, the influence of gamification depends, among other possible factors, on the teacher, also, gamification has no influence on the teaching quality perception in the classroom. These results open important research lines for future works.